PENGARUH PEMBERIAN CAMPURAN KOMPOS KULIT BUAH KAKAO DENGAN KOMPOS TANDAN KOSONG KELAPA SAWIT TERHADAP PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) PADA MEDIUM SUBSOIL ULTISOL - Eric Inmanuel Purba; Ardian Ardian; Sri Yoseva (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The purpose of this research is to determine the effect a mixture of compost cocoa exocarpium with compost TKKS and to get the best treatment combination for the growth of cocoa in the subsoil medium ultisol. This research was conducted in the experimental field and Laboratory of Production Faculty of Agriculture, University of Riau in Campus Binawidya Km 12.5 Simpang Baru Pekanbaru. This research was conducted from March to June 2016. The research used Completely Randomized Design nonfactorial that consisting of 6 treatment and 3 replications, so that there are 18 experimental units. Each experimental unit consisted of three plants and two seeds sampled, so the total crop was 54 plants. Each treatment is : K0 = without compost; K1 = TKKS compost100 g/plant; K2 = cocoa exocarpium compost 25 g/plant + TKKS  compost  75 g/plant ; K3 = cocoa exocarpium compost 50 g/plant + TKKS  compost  50 g/plant ; K4 = cocoa exocarpium compost 750 g/plant + TKKS  compost  25 g/plant ;K5 = cocoa exocarpium compost 100 g/plant. Parameters measured were seedling height, number of leaves, stem diameter, leaf area,root volume and seedling dry weight. Data obtained from the research results were statistically analyzed by analysis of variance followed by a further test of Duncan's New Multiple Range Test (DNMRT) at 5%. Based on the research the application of cocoa exocarpium compostwith TKKS compost on the cocoa seeds that have been carried out, the result showed that the treatment cocoa exocarpium compostwith TKKS compost had significant effect on all parameters of observation. Treatment of cocoa exocarpium compost 100 g/seed can be recommended to get the growth of cocoa’s seedling. Keywords : cocoa, cocoa exocarpium compostwith TKKS compost, Ultisol.